Peran Guru dalam Membentuk Tanggung Jawab Anak Usia Dini melalui Komunikasi Efektif, Empatik, dan Santun - Fitri, Zayyana Zahrotul; Diana, Raden Rachmy (JEA (Jurnal Edukasi AUD), 2023)
The ability to communicate with children is a teacher competency that can support the learning process. Good teacher communication will support the achievement of children's development to be more optimal. This article aims to determine the role of teachers in developing children's responsibility through effective, empathic, and polite communication. The method used is descriptive qualitative, with data collection through observation, interviews, and documentation. The subject of this research is 19 children, class teachers, and accompanying teachers at An-Nur II Kindergarten. Data analysis technique in the form of data reduction, data presentation, and conclusion. Effective communication is seen through an energetic speaking style and supportive body movements. Empathetic and polite communication is seen through responsiveness to children, the use of positive language and a friendly tone, giving appreciation without blaming, and aligning the body when communicating with children. This kind of communication can develop children's responsible behavior. Children are able to follow the teacher's directions, share food, obey the teacher, and listen to the teacher. However, the seating position of children with a group model, the use of mixed language, and the use of media without children exploring it are inhibiting factors in effective communication.